Isu-Isu Berterusan Dalam Pendidikan Matematik - Ahmad Zanzali, Noor Azlan (Penerbit Universiti Sains Malaysia, 1995)
Improving the quality of teaching and learning of mathematics has always been a major concern of mathematics curriculum developers. This paper examines and critically analyzes the following four recurring and inter-related issues often raised in the development of a mathematics curricula in Malaysia:- "What type of mathematics ought to be taught? ", "Why do we need to teach mathematics? ", "How should a mathematics curriculum be planned and arranged?" and "How can teachers ensure that what is transmitted to the pupils is as planned in the curriculum? "